THE INFLUENCE OF AUDITOR INTEGRITY ON INTERNAL AUDIT EFFECTIVENESS WITH AUDITOR COMPETENCE AS A MODERATING VARIABLE - Lidyah, Rika; Purnomo, Purnomo; Patria, Nelly; Hafqi Putri, Eka Lestari; Kusiyah, Kusiyah (ITB AAS Indonesia Surakarta, 2024)
Abstract Researchers believe in two things, namely, first, the Auditor Integrity variable can have a positive relationship and have a significant influence on Internal Audit Effectiveness. Second, researchers determine that the Auditor Competence variable can moderate the influence of the Auditor Integrity variable on Internal Audit Effectiveness. Therefore, this research aims to analyze the influence of the Auditor Integrity variable on the Effectiveness of Internal Auditors with Work Competence as a moderating variable. This research is a quantitative research with an exploratory approach that collects data using a questionnaire method. The data used in this research is primary data. The data was analyzed using the smart PLS 4.0 analysis tool. The research results show that the Auditor Integrity variable has a positive relationship and a significant influence on the Internal Audit Effectiveness variable because the better the Auditor's Integrity, the more independent the auditor, the more likely he is to intervene, and is believed to be able to complete his tasks well. Apart from that, the Audit Competency variable can also moderate the two variable relationships above. Keywords : Auditor Integrity, Internal Audit Effectiveness, Auditor Comptence